Neonatal Outcome of Babies Born to Women 40 Years and Older in a Jamaican Birth Cohort - Trotman, Helen; Samms-Vaughan, Maureen; Coore-Desai, Charlene; Reece, Jody-Ann; Olugbuyi, Oluwayomi (American Journal of Perinatology, 2021)
Objective The study aimed to determine the outcome of babies born to women ≥40 years in a Jamaican birth cohort.Study Design Maternal demographic data and neonatal data for women ≥40 years who delivered live singleton babies and their younger counterparts aged 20 30 years were extracted from the JA KIDS birth cohort dataset. Outcome measures were preterm birth, low birth weight, very low birth weight, extremely low birth weight, macrosomia, a low 5-minute Apgar score <7, admission to the neonatal unit, and neonatal death. Descriptive analyses were performed; statistical significance was taken at the level p <0.05.Results A total of 5,424 women and their babies were entered into the study, 5,099 (94%) women were aged 20 to 30 years (mean age ± standard deviation [SD]: 24.5 ± 3.2 years) and 325 (6%) were aged ≥40 years (mean age ± SD: 41.5 ± 1.6 years). A greater percentage of preterm babies (18%) were born to women ≥40 years than to their younger counterparts (14%; p = 0.04). There was no difference in the proportion of low birth weight infants, very low birth weight infants, or extremely low birth weight infants born between the two groups (p > 0.05). There was also no significant difference in the proportion of babies who were macrosomic and in those who had a low 5-minute Apgar score <7. There were 866 (16%) neonatal admissions, 67/325 (21%) of these babies were born to women aged ≥40 years and 799/5,099 (16%) were born to their younger counterparts (p = 0.01). The commonest reason for admission was prematurity. While 60 babies died, there was no significant difference between both groups with 56 (1%) born to women 20 to 30 years and 4 (1%) born to women ≥40 years (p = 0.48).Conclusion Adverse outcomes noted for babies born to women ≥40 years were prematurity and the need for neonatal admission. However, no excess mortality was recorded.Key Points
Keywords: advanced maternal age; neonatal outcome; low and middle income countries